Fabrication of Hourglass-Shaped Solid-State Nanopores. (19th February 2016) - Li, Xiao-Ning; Li, Yu-Xing; Yang, Yi; Wang, Gang; Liu, Hou-Fang; Mohammad, Mohammad Ali; Qiu, Hao-Chuan; Ren, Tian-Ling
Abstract : Solid-state nanopore devices hold great promise for the rapid characterization of biomolecules. Here we present a simple technique that can efficiently and flexibly fabricate a large number of solid-state nanopore arrays and nanotrenches with hourglass-like inner morphology at low cost based on the step coverage feature of PECVD (plasma enhanced chemical vapor deposition). Nanopores with dimensions of 19 nm × 45 nm and nanotrenches as small as 7 nm were successfully fabricated. These results show that this technique has the potential to fabricate uniform nanopore arrays with hourglass-like inner morphology in mass production, which can be applied to the parallel analysis of biomolecules.